Investment and benefits associated with community based forest enterprises in Nepal - Dhakal, S. R.; Sharma, A. R.; Paudel, G. (Banko Janakari, 2018)
Community forests in Nepal are operating various types of forest-based enterprises. These enterprises are generating considerable amount of income and employment at the local level contributing to the local and national economy. Comprehensive assessment of these enterprises is needed to improve their condition in the future. There is lack of assessment on the investment and benefits associated with these enterprises. We collected the data from 195 community-based enterprises in 23 districts of Nepal representing all geographic and development regions. For the analysis purpose, we categorized the enterprises into four categories viz. non-timber forest products (NTFPs), wood, ecotourism and agriculture enterprises. We analysed the investment, income, households benefitted and employment generation from these enterprises and compared with each other. Mean investment in ecotourism (US 22805.09) and wood (US 11252.42) based enterprises was found higher than the mean investment in NTFPs (US 2628.03) and agriculture (US 3383.63) based enterprises. Mean annual income from the enterprises was found US 1982.56 and was significantly different between the types of enterprises (P<0.05). On an average 115 households were benefitted per enterprise. Employment generation from wood based (2527 man-days) enterprises was found the highest followed by ecotourism (1490 man-days) enterprises. The mean employment generation from NTFP (1093 man-days) and agriculture-based enterprises (978 man-days) was found significantly lower (P<0.05) than timber and ecotourism-based enterprises. Examination of community-based forest enterprises contribution in local economy and household economy is recommended for future researchers.